DEFICIENCY ANEMIAS IN EARLY CHILDHOOD: IRON DEFICIENCY ANEMIA (Multidisciplinary Journal of Science and Technology, 2025)
The article presents a literature review of modern trends in the diagnosis and treatment of iron deficiency anemia in children. The forms of iron deficiency are determined, the causes of development and criteria for laboratory diagnostics are given, a modern view on the choice of drugs for the treatment of children with iron deficiency anemia.